2014
DOI: 10.7314/apjcp.2014.15.2.1041
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin Promotes c-Jun N-terminal Kinase Mediated Apoptosis via a GABABR·β-arrestin·JNK Signaling Module

Abstract: Asian Pac J Cancer Prev, 15 (2), 1041-1046 IntroductionAs one of the most common types of cancer, breast cancer represents the most prevalent and lethal malignancy among female. Its incidence in China has gradually increased accompanied with the changes in people's lifestyle (Wang et al., 2013). Despite developments in surgery and the increased number of drugs for radio-and chemotherapy, post-operative morbidity and other health problems significantly reduced the life quality of patients (Li et al., 2013). Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, the analysis of TCGA (The Cancer Genome Atlas) and METABRIC (Molecular Taxonomy of Breast Cancer International Consortium) datasets reveal that βarr1 expression is downregulated in TNBC patient samples, further underscoring its role as a potential tumor suppressor in breast cancer (Son et al, 2019). Wu et al have reported that in MCF-7 and T-47D breast cancer cell lines, the levels of βarr2 is lower compared to corresponding control cell lines, and βarr2 overexpression inhibits proliferation of these cells and triggers apoptosis (Wu et al, 2014). The contribution of βarr2 in this context involves GABA-B receptor and activation of JNK kinase (Wu et al, 2014).…”
Section: Role Of β-Arrestins In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the analysis of TCGA (The Cancer Genome Atlas) and METABRIC (Molecular Taxonomy of Breast Cancer International Consortium) datasets reveal that βarr1 expression is downregulated in TNBC patient samples, further underscoring its role as a potential tumor suppressor in breast cancer (Son et al, 2019). Wu et al have reported that in MCF-7 and T-47D breast cancer cell lines, the levels of βarr2 is lower compared to corresponding control cell lines, and βarr2 overexpression inhibits proliferation of these cells and triggers apoptosis (Wu et al, 2014). The contribution of βarr2 in this context involves GABA-B receptor and activation of JNK kinase (Wu et al, 2014).…”
Section: Role Of β-Arrestins In Breast Cancermentioning
confidence: 99%
“…Wu et al have reported that in MCF-7 and T-47D breast cancer cell lines, the levels of βarr2 is lower compared to corresponding control cell lines, and βarr2 overexpression inhibits proliferation of these cells and triggers apoptosis (Wu et al, 2014). The contribution of βarr2 in this context involves GABA-B receptor and activation of JNK kinase (Wu et al, 2014). Another study has observed overexpression of an orphan GPCR, Gpr161, in MDA-MB-361 and BT-474 cells (Feigin et al, 2014).…”
Section: Role Of β-Arrestins In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The GABAB receptor is involved in tumorigenesis; b-arrestin recruits JNK to the GABAB receptor, where it is activated and reduces the growth of cancer cells. This same method of JNK activation promotes cell apoptosis in breast cancer cells (Wu et al, 2014). In Drosophila, Kurtz is a non-visual arrestin equivalent that couples Methuselah (MTH), a GPCR required for neurosecretion, with JNK, thus mediating stress-resistance and longer life (Gimenez et al, 2013).…”
Section: Plenty Of Sh3s Protein (Posh) and B-arrestinmentioning
confidence: 99%